Analisis Faktor yang Mempengaruhi Keterampilan Berbicara Selama Proses Pembelajaran Mahasiswa - Azza Dhifa Zayyan Hanifa; Heri Saptadi Ismanto; Agus Setiawan (Journal Prakarsa Paedagogia, 2022)
The low speaking skills possessed by students such as, insecurity and nervousness when dealing with many people, this makes students stammer so that they often say the word "a../e..". Some students will divert nervousness by moving their hands / feet, some are staring at the corners of the room. Then the lack of mastery of the material is also a factor in students not being confident and nervou. This type of research uses qualitative research with a case study method. Data collection used are interview guidelines, questionnaires and documentation. Then the data that has been obtained is analyzed through the stages of four components, namely data collection, data reduction, data presentation and conclusion drawing, which is then presented in the form of descriptions in sentence form regarding the discovery of the meaning of each phenomenon.Based on the results of the data analysis, there are several factors that influence students' speaking skills, namely a reasonable attitude, calm and not rigid, the gaze must be directed to the interlocutor, willingness to respect other people's opinions, appropriate gestures and mimics, fluency, relevance / reasoning and mastery of the topic. Then there are still many students who have not been able to master these skills.